Upaya meningkatkan minat belajar siswa dengan menggunakan pendekatan project Based learning pada siswa kelas VIII SMP Negeri 6 Padangsidimpuan - yuni fitri febriani; Adek Nilasari Harahap; Andi Saputra Mandopa (Program Studi Matematika Universitas Graha Nusantara Padangsidimpuan, 2024)
The research method used is classroom action research utilizing two cycles conducted in the second semester with the material of Geometry and Spatial Structures using the Project-Based Learning approach. The sample in this study is students in class VIII^1 at SMP Negeri 6 Padangsidimpuan, totaling 32 students. The results of the study indicate that the interest in learning Mathematics through the Project-Based Learning method among grade VIII^1 students at SMP Negeri 6 Padangsidimpuan in the 2023/2024 academic year increased. This can be seen from the increase in the average initial test score of 57.34%. The students’ learning interest test scores in cycle I meeting I were 66.6 and in meeting II were 80 with an average score of 73.3%. In cycle II meeting III, the students’ learning interest test scores were 86.6 and in meeting IV were 100 with an average score of 93.3%. Meanwhile, the results of the teacher’s observations in cycle I meeting I were 66.6 and in meeting II were 79.1 with an average score of 72.85. In cycle II meeting II, the teacher’s observation results were 83.33 and in cycle IV were 95.83 with an average score of 89.55%.